Cultural Arts Learning at Senior High School 7 Tanjung Jabung Barat - Zarizdu, Depi; Harisnal Hadi (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2024)
This study aims to determine and describe the Learning of Cultural Arts (Tari) at the State High School 7 Tanjung Jabung West. The type of research used in this research is qualitative using the descriptive method. The subject of this study was Cultural Arts and students in the XI IPS-A State High School 7 Tanjung Jabung West. While the object in this study is Cultural Arts Learning for students of XII IPS-A at the State Senior High School 7 Tanjung Jabung Barat. The types used in this study are primary data and secondary data. Research instruments in this study were its own researchers or human instruments assisted by some tools to collect data, including stationery and notebooks and ynag cameras are useful to take gamber. Data collection techniques in this study are observations, interviews, documentation and literature studies.Based on the results of the research and discussion, it is concluded that the learning process is quite satisfying by RPP, designed and the results of students’ grades are quite satisfying. However, students feel monotonous learning for teaching methods only by preaching methods, students tend to understand materials independently and worksheets of students, so that they need to be given innovation when given media such as watching learning videos to increase students’ learning motivations to be more effective and attractive.